Cymbopogon citratus essential oil has hepato/renal protection and anti-genotoxicity against carbon tetrachloride - Fahmy, Maha Aly; Aly, Fawzia Abd Elfatah; Hassan, Emad Mohamed; Farghaly, Ayman Ali; Hassan, Entesar Elsayed; Samea, Negm Sayed Abdel (Comunicata Scientiae, 2020)
Nowadays, there is an increasing trend to use aromatherapy for treatment of various diseases. Cymbopogon citratus (Lemongrass) is one of many plants which have been reported to employ successfully in aromatherapy. Herein we decided to explore the protective role of Cymbopogon citratus essential oil (CCEO) against hepato/renal damage and genotoxicity induced by carbon tetrachloride (CCl4) and the relation of this bioactivity with its chemical constituents. Six main groups of mice (five/each) were examined: I- represents negative control group, II and III- mice received oral treatment with CCl4 (1mL/kg, positive control) and CCEO (0.3 mL/kg, control plant) respectively for five consecutive days and IV-VI- represent groups of mice treated with CCEO at the three concentrations 0.1, 0.2, 0.3 mL/kg plus CCl4 (five consecutive days treatment). Remarkable adverse effects of CCl4 in all the tested parameters were recorded. These effects were distinguished as an increment in the level of all liver marker enzymes (ALT, AST, ALP, γ-GT), blood urea, and creatinine. Also the oxidative stress biomarkers: malondialdehyde (MDA) and glutathione-transferase GST were affected after CCl4 treatment. Regarding to the genotoxic effect of CCl4, the percentage of chromosomal aberrations in bone marrow and spermatocyte cells was elevated (p< 0.05) compared with the negative control. Notable antioxidant, hepato/renal protection and anti-mutagenic potency of CCEO against CCl4 were demonstrated with a dose-related relationship. GC/MS analysis demonstrated the presence of 12 phytochemical constituents which in combination play a critical role in its antioxidant/antigenotoxic efficacy. The major components exist were E. Citral (35.13%) and Geraniol (32.83%).